2023
DOI: 10.21203/rs.3.rs-2621281/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of the Xigaze Metamorphic Sole under the Tibetan continental margin reveals generic characteristics of the subduction initiation process

Abstract: Metamorphic soles found under allochthonous oceanic lithosphere, or ophiolites, are derived from the earliest lower plate oceanic crust accreted to upper plate mantle and are considered diagnostic of intraoceanic subduction initiation. Their metamorphic evolution is inferred to reflect the thermal structure at the site of subduction nucleation, with granulite-bearing soles linked to initiation at hot spreading centers. Here we present garnet Lu-Hf geochronology for the granulite-bearing sole of the Xigaze ophi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…With no clear exception, and regardless of rock composition, mineral assemblage or metamorphic grade, Lu‐Hf garnet ages are similar to, or older than, the accessory mineral U–Pb ages that are interpreted to date peak metamorphism (Figure 1b). The data thus do not reflect down‐skewing of Lu‐Hf ages, as predicted for garnet‐clinopyroxene assemblages (Bloch et al, 2015), and in fact can be readily interpreted to reflect the nature of garnet as a prograde mineral that typically forms earlier in the petrogenetic history of metamorphic rocks than zircon or monazite (e.g., Anczkiewicz et al, 2007; Godet et al, 2021; Guilmette et al, 2018; Guilmette et al, 2023; Smit, Hacker, & Lee, 2014) and may even retain age information on metamorphic events that accessory minerals appear to have missed (e.g., Lihter et al, 2022; Thiessen et al, 2019). Although these data generally indicate the robustness of Lu‐Hf ages, they do not exclude that Lu diffusion affects such ages in individual cases.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…With no clear exception, and regardless of rock composition, mineral assemblage or metamorphic grade, Lu‐Hf garnet ages are similar to, or older than, the accessory mineral U–Pb ages that are interpreted to date peak metamorphism (Figure 1b). The data thus do not reflect down‐skewing of Lu‐Hf ages, as predicted for garnet‐clinopyroxene assemblages (Bloch et al, 2015), and in fact can be readily interpreted to reflect the nature of garnet as a prograde mineral that typically forms earlier in the petrogenetic history of metamorphic rocks than zircon or monazite (e.g., Anczkiewicz et al, 2007; Godet et al, 2021; Guilmette et al, 2018; Guilmette et al, 2023; Smit, Hacker, & Lee, 2014) and may even retain age information on metamorphic events that accessory minerals appear to have missed (e.g., Lihter et al, 2022; Thiessen et al, 2019). Although these data generally indicate the robustness of Lu‐Hf ages, they do not exclude that Lu diffusion affects such ages in individual cases.…”
Section: Introductionmentioning
confidence: 93%
“…Observations made from natural garnet generally indicate that REE diffusion in natural garnet is relatively sluggish. Garnet that has undergone long‐lived thermal overprinting during high and ultrahigh‐temperature ( HT ; UHT ) metamorphism commonly preserves strong REE zoning (e.g., Carlson, 2012; Cutts & Smit, 2018; Guilmette et al, 2018; Guilmette et al, 2023; Pownall et al, 2019; Pyle & Spear, 2000; Rubatto et al, 2020; Smit, Ratschbacher, et al, 2014). Estimates of REE diffusivities constrained from diffusion zoning in natural garnet are lower than those determined in most experiments (Carlson, 2012) and are approximated only by REE diffusivities determined in a high‐pressure diffusion experiment (van Orman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since transform fault‐related SI proposed by the SIR creates intraoceanic subduction and suture zones perpendicular to the ridges, it contradicts the kinematics and plate configurations of the Jurassic western Neo‐Tethys Ocean (Maffione, Thieulot, et al., 2015). On the other hand, multiple lines of evidence have also suggested that some Early Cretaceous ophiolites in the eastern Neo‐Tethys (such as the Yarlung Tsangpo ophiolites in southern Tibet) were generated in a tectonic location quite close to the continental margin (e.g., Guilmette et al., 2023; Huang et al., 2015), which disagrees with the spontaneous intraoceanic SI at transform faults or fracture zones in the SIR model. Ridge‐ and/or continental margin‐parallel SI should therefore be considered for the generation of the abovementioned Neo‐Tethyan ophiolites in the geological history of both the Jurassic (Maffione, Thieulot, et al., 2015; van Hinsbergen et al., 2015) and Early Cretaceous (Guilmette et al., 2023; C. Zhang et al., 2019).…”
Section: Introductionmentioning
confidence: 95%